RING1 is associated with the polycomb group protein complex and acts as a transcriptional repressor. - Satijn, D P (1997)
The Polycomb (Pc) protein is a component of a multimeric, chromatin-associated Polycomb group (PcG) protein complex, which is involved in stable repression of gene activity. The identities of components of the PcG protein complex are largely unknown. In a two-hybrid screen with a vertebrate Pc homolog as a target, we identify the human RING1 protein as interacting with Pc. RING1 is a protein that contains the RING finger motif, a specific zinc-binding domain, which is found in many regulatory proteins. So far, the function of the RING1 protein has remained enigmatic. Here, we show that RING1 coimmunoprecipitates with a human Pc homolog, the vertebrate PcG protein BMI1, and HPH1, a human homolog of the PcG protein Polyhomeotic (Ph). Also, RING1 colocalizes with these vertebrate PcG proteins in nuclear domains of SW480 human colorectal adenocarcinoma and Saos-2 human osteosarcoma cells. Finally, we show that RING1, like Pc, is able to repress gene activity when targeted to a reporter gene. Our findings indicate that RING1 is associated with the human PcG protein complex and that RING1, like PcG proteins, can act as a transcriptional repressor.